Ferroptosis and noncoding RNAs: exploring mechanisms in lung cancer treatment - Rostami Ravari, Nadi; Sadri, Farzad; Mahdiabadi, Mohammad Ali; Mohammadi, Yaser; Ourang, Zahra; Rezaei, Zohreh (Frontiers in Cell and Developmental Biology, 2025)
Lung cancer (LC) is a highly prevalent and deadly type of cancer characterized by intricate molecular pathways that drive tumor development, metastasis, and resistance to conventional treatments. Recently, ferroptosis, a controlled mechanism of cell death instigated by iron-dependent lipid peroxidation, has gained attention for its role in LC progression and treatment. Noncoding RNAs (ncRNAs), such as microRNAs (miRNAs) and long noncoding RNAs (lncRNAs), are emerging as key modulators of ferroptosis, significantly influencing LC biology. This review explores how ncRNAs control ferroptotic pathways and affect tumor growth, metastasis, and therapy resistance in LC. By understanding the dual functions of ncRNAs in both activating and inhibiting ferroptosis, we aim to uncover new therapeutic targets and strategies for LC. These insights provide a promising direction for the development of ncRNA-based treatments designed to induce ferroptosis, potentially improving therapeutic outcomes for patients with LC.